2018
DOI: 10.1016/j.ejmech.2018.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazole carbamates and amides as antiproliferative species

Abstract: A series of new benzothiazole-based carbamates and amides were synthesized and their antiproliferative activity was determined. Derivatives with profound activity were identified and further investigated for their possible mechanism of action. It was found that these compounds induce specific apoptosis, G2/M cell cycle arrest and decrease ROS level in MCF-7 human breast cancer cell line. Moreover, submicromolar antiproliferative activity of examined carbamates against NT2/D1 testicular embryonal carcinoma was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…BTA derivatives have been widely used in the development of antitumor drugs, especially molecularly targeted antitumor drugs, because of their easy synthesis 26 . One study found that the benzothiazole derivative carbamate showed antiproliferative activity against NT2/D1 cells 27 . And a report found that AFN01 (benzothiazole derivative) inhibited cell proliferation in a model gastric cancer cell line 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTA derivatives have been widely used in the development of antitumor drugs, especially molecularly targeted antitumor drugs, because of their easy synthesis 26 . One study found that the benzothiazole derivative carbamate showed antiproliferative activity against NT2/D1 cells 27 . And a report found that AFN01 (benzothiazole derivative) inhibited cell proliferation in a model gastric cancer cell line 28 .…”
Section: Discussionmentioning
confidence: 99%
“…26 One study found that the benzothiazole derivative carbamate showed antiproliferative activity against NT2/D1 cells. 27 And a report found that AFN01 (benzothiazole derivative) inhibited cell proliferation in a model gastric cancer cell line. 28 In this study, we examined the responses of OVCAR420 and SKOV3 cells to different concentrations of Rosline.…”
Section: Discussionmentioning
confidence: 99%